ANALISIS PERSISTENSI INFLASI DAERAH: STUDI KASUS SUMATERA BARAT - Agung Bayu Purwoko; Feny Yurastika (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2011)
Bank Indinesia replaced base money targeting with inflation targeting framework (ITF) since July 2005. Thus understanding inflation persistence is important to support the effectiveness of this framework. This study attempts to understand the behavior of inflation persistence of regional level, completing several studies conducted at the national level. Specifically, this study aims to cal -culate the level of inflation persistence in West Sumatera, to see how the effect of inflation targeting framework on inflation persistence, and to find the sources of inflation persistence. Using univariate model AR, we find that inflation persistence in West Sumatera is high. When we break the period into before and after the implementation of ITF, it indicates that inflation persistence decrease after the implementation of ITF. However, this difference is not statistically significant. Using Hybrid New Keynesian Philips Curve (NKPC), we find that the behavior of inflation is dominated by ackward looking inflation. Overall results showed that inflation problem can not be resolved only through monetary policy. Despite, monetary policy through ITF framework is still necessary to achor agents’ expectation still stronger coordination between cen -tral bank and local government must be developed to reach common goal of inflation.